Metal halide perovskite nanomaterials: synthesis and applications - Ha, Son-Tung (2017)
Nanomaterials refer to those with at least one dimension being at the nanoscale (i.e. <100 nm) such as quantum dots, nanowires, and nanoplatelets. These types of materials normally exhibit optical and electrical properties distinct from their bulk counterparts due to quantum confinement or strong anisotropy. In this perspective, we will focus on a particular material family: metal halide perovskites, which have received tremendous interest recently in photovoltaics and diverse photonic and optoelectronic applications. The different synthesis approaches and growth mechanisms will be discussed along with their novel characteristics and applications. Taking perovskite quantum dots as an example, the quantum confinement effect and high external quantum efficiency are among these novel properties and their excellent performance in applications, such as single photon emitters and LEDs, will be discussed. Understanding the mechanism behind the formation of these nanomaterial forms of perovskite will help researchers to come up with effective strategies to combat the emerging challenges of this family of materials, such as stability under ambient conditions and toxicity, towards next generation applications in photovoltaics and optoelectronics.